Development of prefabricated composite energy-dissipating slotted shear wall. (15th November 2019) - Shen, Shao-Dong; Cui, Yao; Pan, Peng; Ren, Jun-Yu
Highlights: A dual system that combines prefabricated slotted walls with a frame was proposed. A composite energy-dissipating slotted shear wall (CDSW) was proposed. Quasi-static test was performed to study the seismic behavior of the CDSW. A modified D-value method for designing slotted shear walls was proposed. Abstract: In a wall-frame system, shear walls are considered to be components with high load-bearing capacity and stiffness to provide lateral resistance. However, the ductility of shear walls is commonly far weaker than the frame. When high deformation is generated in a structure during earthquakes, shear walls are often damaged whereas the frame remained intact, which leads to their uncoordinated and restricted deformation. Furthermore, insufficient energy dissipation is exhibited within the limited deformation. This study is aimed at developing an innovative composite energy-dissipating slotted shear wall (CDSW). The CDSW features concrete-filled-tube wall segments, vertical slots, and H-shaped soft steel connectors, and it is endowed with significantly elevated deformability and energy dissipation. A quasi-static test was performed to investigate the seismic behavior of the CDSW, which showed high ductility. Finally, based on the calculation process of the conventional D-value method for frame structures, a modified D-value method was proposed to calculate the internal force and strength of slotted shear walls. The skeleton curve of the CDSW calculated by the modified D-value method agreed well with that obtained from the testing.